CASE STUDY OF PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY IN THE WORK AREA OF BURNEH COMMUNITY HEALTH CENTER, BANGKALAN REGENCY: CASE STUDY OF PREGNANT WOMEN WITH CHRONIC ENERGY DEFICIENCY IN THE WORK AREA OF BURNEH COMMUNITY HEALTH CENTER, BANGKALAN REGENCY - Marsyanda Riskia Tristiana; Anis Nurlaili, S.SiT,M.Keb; Siti Anisak, S.Keb., Bd., M.Keb (Fetus : Journal of Midwifery, 2025)
Pregnant women with chronic energy deficiency (CED) can be identified by a mid-upper arm circumference (MUAC) of ≤ 23.5 cm. This case study aims to identify risk factors (age, education, nutritional intake, parity, occupation, and family income), problems encountered by pregnant women with CED (FUL and LBW), and efforts made by pregnant women to manage CED. The incidence of CED at the Burneh Community Health Center in 2023 was 27 (3.1%) out of a total of 855 pregnant women.   This case study used a multiple case design with two respondents meeting the same criteria: pregnant women with a mid-upper arm circumference (MUAC) of ≤ 23.5 cm. The study was conducted in the Burneh Community Health Center's work area from March to April 2024. Data collection tools included interviews, observation, and documentation. Respondents were from Langkap and Binoh villages.   The case study results revealed that both respondents shared a risk factor, namely infectious diseases (gastritis). Respondents 1 and 2 both had FUL and LBW inappropriate for gestational age. Both respondents regularly took iron tablets. Respondent 1 regularly attended prenatal classes, while respondent 2 never attended.   CED in pregnant women can be prevented if mothers adhere to a nutritious diet and regularly take iron tablets. It is hoped that mothers will increase their nutritional needs to ensure they have sufficient nutrients for both themselves and their fetus.   Keywords: pregnant women, CED, risk factors, TFU and TBJ